Os índices cronotópicos no discurso poético de Sérgio de Castro Pinto: uma análise discursiva - Santos, Aline Cardoso (2020)
This dissertation work intends to examine the manifestation of chronotopic indexes in fifteen poems by the contemporary paraiban poet Sérgio de Castro Pinto (1983), in the light of the postulated dialogical theory of discourse (TDD) by Bakhtin (2011, 2014) and the Circle. Thus, this work seeks, specifically, to enter into the analysis of the discourse manifested in the poetry of the paraiban poet Sérgio de Castro Pinto based on the theoretical-philosophical discussions of Bakhtin (2014), Tezza (2003) and Ladin (2015). Seeking to delineate the Bakhtinian additions to the study of poetry in contrast to the analyzes developed in the light of the formal method. Concomitantly, we seek to expand and foster the analysis of the work of one of the national representatives of Paraíba's poetry to those works that, recently, focus on chronotopic analysis in poetic texts. In order to articulate understandings about fundamental aspects of TDD, we spoke with the Bakhtinian interlocutors: Brait (2013), Sobral (2009), Faraco (2009) and Fiorin (2016). Thanks to the study of chronotopic indexes, we observed from this category that poems can also be constituted by a discourse full of ideological questions, especially when accentuated by the historical outline. The analyzes developed in this research showed the presence of historical - ideological chronotopic loads in the poetic discourse, in addition, we conclude that each book of poems establishes in itself a larger chronotope, the book is the chronotope that brings together the poems and their smaller chronotopes in which there is the creation of microchronotopes that correlate in each poem the indices of places, feelings or historical - ideological traits.